LEVEL SHIFTS IN TOETY HERATY'S 'GENEVA BULAN JULI' POETRY TRANSLATION - Ni Putu Sita Vallabha; Putu Desi Anggerina Hikmaharyanti (UIN Raden Mas Said Surakarta, 2025)
Poetry often uses certain linguistic devices and styles such as metaphors, meters, and rhymes. A level shift can occur when these devices are expressed differently in the target language. Different languages have varying grammatical structures and rules, which can lead to level shift when translating. Cultural and contextual differences may require a level shift to make the poem understandable and comprehensible in the target language. In shift translation, there are two categories, level shift and category shift. This study focuses on the identification of the level shift in the poem Geneva Bulan Juli and its translation. A qualitative descriptive method is used to analyze the data of this study. The result shows that there are 17 level shifts occurring with the majority in the forms of shifts from grammatical forms, in the source language, to lexical forms, in the target language. These shifts include the transformations of verbs to nominal forms, the removals or additions of time elements and aspects, and the replacements of complex syntactic structures into dense and direct diction. Each shift serves not only as a linguistic adjustment but also as a rhetorical strategy to maintain the depth of meanings, emotional nuances, and poetic power in translation. These findings suggest that level shifts are inevitable strategies as well as creative aspects in poetry translation that have important implications for the studies of cross-cultural literary translation.